2018
DOI: 10.1039/c7cc09140k
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for generating aryl radicals from arylborates through organic photoredox catalysis: photo-Meerwein type arylation of electron-deficient alkenes

Abstract: Photoinduced reactions of arylboronic acids with electron deficient alkenes under mild organic photoredox catalysis conditions lead to the formation of Meerwein arylation type adducts via the generation of aryl radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…6a). As transient aryl radical can be trapped by TEMPO 52 , the fact that no trapping of the aryl radical with TEMPO indicated that the radical cyclization step might be fast. Second, we did isotope-labeling studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6a). As transient aryl radical can be trapped by TEMPO 52 , the fact that no trapping of the aryl radical with TEMPO indicated that the radical cyclization step might be fast. Second, we did isotope-labeling studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the aim of developing synthetic approaches that utilize less toxic and more readily available reagents under mild conditions, we have been investigating photochemical reactions using organic photoredox catalysts, as they constitute environmentally friendly methods wherein light is applied as a traceless reagent, and harsh reaction conditions, such as high temperature and pressure, are not required. We have recently reported photoinduced electron transfer (PET)-promoted reactions of carboxylic acids [21][22][23][24][25][26][27], arylboronic acids [28], indene [29,30], and electron-rich alkenes [31] catalyzed by two-molecule organic photoredox catalysts, such as a combination of phenanthrene (Phen) as an electron donor and 1,4-dicyanobenzene (1,4-DCB) as an electron acceptor, under UV irradiation (313 nm) (Scheme 1b). This finding encouraged us to explore the PET-promoted decarboxylation of amino acids and peptides for their modification [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…[29] Recently,L ey and co-workers described an acridinium photocatalyzed oxidative generation of alkyl radicals from R-Bpin /dimethylaminopyridine complexes using flow technology. [30] Other ate complexes such as alkyl trifluoroborates, and organo(triol)borates, [34,35] and boronic acids [30,56,[61][62][63][64] have also been successfully oxidized to deliver the corresponding alkyl radicals using either electrochemical, chemical, or photoredox-catalyzed oxidation. [65] Based on the preliminary results described in Scheme 1A, we report here particularly simple conditions to furnish radicals from avariety of different pinacol alkylboronic esters made possible by an in situ transesterification.…”
Section: Introductionmentioning
confidence: 99%